ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF THE AUDITOR INSPECTORATE OF NORTH SUMATRA PROVINCE WITH AUDITOR INDEPENDENCE AS A MODERATING VARIABLE - Tuti Rahmawati; Keulana Erwin; Muammar Khaddafi (CV. Radja Publika, 2023)
This research aims to determine the factors that influence the performance of inspectorate auditors in North Sumatra province with auditor independence as a moderating variable. This type of research is causality research, namely research that aims to analyze possible cause-and-effect relationships based on observations. This research was conducted using primary data with a survey method obtained through distributing questionnaires to auditors. The results of this research are that the first hypothesis is accepted, the Experience variable (X1) has a significant effect on the Auditor Performance variable (Y). The second hypothesis is accepted, the Knowledge variable (X2) has a significant effect on the Auditor Performance variable (Y). The third hypothesis is rejected, The Auditor Motivation variable (X3) has no significant effect on the Auditor Performance variable (Y). The fourth hypothesis is accepted, meaning that Experience (X1), Knowledge (X2), Auditor Motivation (X3) and Independence (Z) have a significant effect together (simultaneously) on the Auditor Performance variable (Y). The fifth hypothesis is accepted. The Independence variable (Z) is a moderator variable that influences the relationship between Experience (X1) and Auditor Performance (Y). The sixth hypothesis is accepted. The Independence variable (Z) is a moderator variable that influences the relationship between Knowledge (X2) and Auditor Performance (Y). The seventh hypothesis is rejected. The independence variable (Z) is not a moderator variable that influences the relationship between Auditor Motivation (X3) and Auditor Performance (Y). In order for the experience of auditors at the North Sumatra Provincial Inspectorate to be of higher quality, it is best to pay attention to the level of education and provide training regarding the implementation of audits and understanding the regulations as an auditor. So that auditors understand better and can carry out their duties well, because the knowledge and education obtained to audit requires a lot of experience. Apart from that, an auditor will learn a lot from the various cases he handles so that the auditor's performance can be of high quality. because the knowledge and education obtained to audit requires a lot of experience. Apart from that, an auditor will learn a lot from the various cases he handles so that the auditor's performance can be of high quality. because the knowledge and education obtained to audit requires a lot of experience. Apart from that, an auditor will learn a lot from the various cases he handles so that the auditor's performance can be of high quality.